“Relaciones laborales entre las secretaria/os, directivos y jefes departamentales de las instituciones de educación media del cantón Latacunga, año 2014” - Molina Cela, Mayra Fernanda (2015)
The purpose of this research work is to improve the labor relations between the secretaries, directors and departmental Heads of the Institutions of Secondary Education of the Latacunga canton, for the year 2014, which allowed to improve the working relationship between the investigated parties, this plan contributes to labor harmony, resulting in the emotional stability of the employee and employer. The investigation made it possible to identify the lack of communication between the personnel of the various institutions, which affects labor relations and their performance. The current study was developed based on field research, libraries and websites, allowing to feel the reality of the problem posed.